Frequency and antimicrobial resistance of bacteria isolated from oral and topical medicaments from Hilla, Iraq - Alaa Hani Al-Charrakh (Journal of Infection in Developing Countries)
Introduction: The presence of microorganisms in pharmaceuticals is undesirable because they may cause spoilage of the product and may present an infection hazard to the consumers or patients.